2011
DOI: 10.1039/c0cc04126b
|View full text |Cite
|
Sign up to set email alerts
|

Controlled manipulation of multiple cells using catalytic microbots

Abstract: Self-propelled microjet engines (microbots) can transport multiple cells into specific locations in a fluid. The motion is externally controlled by a magnetic field which allows to selectively load, transport and deliver the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
251
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(257 citation statements)
references
References 21 publications
2
251
0
4
Order By: Relevance
“…[9][10][11] Previous studies have also indicated the facile motion of polymer-based micromotors or rolled up microjets in various diluted (3-4 fold diluted) real-life media. [12][13][14][15][16][17][18] However, recent reports claimed that the movement of bubble-propelled Cu-Pt microengines is greatly hindered in various diluted real samples, and even completely stopped in highly diluted serum or seawater. 19,20 Such observations may have profound implications on the scope of future applications of microscale machines.…”
mentioning
confidence: 99%
“…[9][10][11] Previous studies have also indicated the facile motion of polymer-based micromotors or rolled up microjets in various diluted (3-4 fold diluted) real-life media. [12][13][14][15][16][17][18] However, recent reports claimed that the movement of bubble-propelled Cu-Pt microengines is greatly hindered in various diluted real samples, and even completely stopped in highly diluted serum or seawater. 19,20 Such observations may have profound implications on the scope of future applications of microscale machines.…”
mentioning
confidence: 99%
“…Because microjets rely on fuel ingression into a tubular structure, these examples are highly sensitive to surface tension and need the addition of surfactants in order to decrease the surface tension and allow fuel ingression. [ 14,[46][47][48][49][50][51][52][53][54] Likewise, the majority of the reported spherical micromotors either need addition of a surfactant in order to achieve propulsion, [ 6,7,10,55,56 ] or alternatively propulsion has only been demonstrated in a specifi c non-aqueous solvent system. For some of these examples, biocompatibility was also specifi cally assessed by measuring motion within fl uids such as serum, and again surfactants were required in order for motion to be produced.…”
mentioning
confidence: 99%
“…Wang and co-workers [ 49 ] Ti/Ni/Au/Pt (microjets) Yes 125 µm s Pumera and co-workers [ 51 ] Cu/Pt (microjets) Yes 365 µm s −1 3% H 2 O 2 Sanchez et al [ 52 ] Ti/Fe/Pt (microjets) Yes 130 µm s −1 4% H 2 O 2 in 25% cell medium Sanchez et al [ 53 ] Ti/Cr/Pt (microjets) Yes 500 µm s…”
mentioning
confidence: 99%
“…Many researchers proposed the utilization of biodegradable magnetic nanoparticles [3], [4], magnetotactic bacteria [5], artificial swimmers [6], and self-propelled microjets [7], [8] to execute limited tasks, such as targeted drug delivery [9], microassembly [10], and microactuation [11]. Realization of a reliable drug targeting system necessitates the development of precise closed-loop motion control systems.…”
Section: Introductionmentioning
confidence: 99%